Connection and competition: some early insights gained from petrographic studies of New Caledonian Lapita pottery. Issue 2 (5th April 2016) - CHIU, SCARLETT; KILLICK, DAVID; SAND, CHRISTOPHE; DICKINSON, WILLIAM R.
ABSTRACT: Results of petrographic analysis for ten New Caledonian Lapita pottery assemblages are presented in this paper. These findings enable us to identify several major pottery production areas during the Lapita period. It could be argued that the rise of pottery production traditions at the northern bank of the Diahot Valley near Ouégoa/Pouébo in the north, and the region between Tontouta and Nouméa/Saint Louis in the south, was influential in the formation of the northern versus southern New Caledonian cultural divisions (Sand et al .: 64‐5, fig. 11) that developed at a later date.